RANCANGAN DAN ANALISIS SISTEM INFORMASI GUDANG STUDI KASUS SERAMBI BOTANI ORGANIK - Roelly Humdiana, S.Kom., MM., M.Kom (Jurnal Informatika dan Bisnis, 2013)
The Technology development is now rapidly, our life can’t be rid of technology, advance of anyeffort area too can’t be rid of technology, technology help to increase effort activity, one ofrelated to technology is Management Warehouse Information System. Application for SerambiBotani developed using Visual Basic Programming Language for the system and SQL SERVERfor the database. Information Collection was conducted by interview Serambi Botani Managerand observation. Application designed by using prototyping. The results of this research isApplication of Serambi Botani Warehouse that probably user to do writing item data, itemsending, and do purchasing quickly and structured. With this application operational work ofSerambi Botani Warehouse will be effective and effisient, manager and owner can accessing andcontrolling flow of transaction, and any giving assignment will be controlled.